Management of Character Education Strengthening Strategies in Students - Sutarman,; Widiastuti, Ika; Badriatin, Tine; Arofah, Irvana; Syahriani, (International Journal of Psychosocial Rehabilitation, 2020)
Management of Student Character Education Strategies in schools. An education system that focuses on religion, by integrating science and religion, using strategic management analysis in an effort to shape the character of students, and human character in general. Form superior individuals, become complete human beings, who are able to show their own self-image. All students are able to complete everything he answers, become a different person and excel in intelligence and intelligence, intelligence intelligence, and spiritual intelligence, from the intelligence of the character, from intelligence that will form an educated character, become a strong and superior person. The aim is to make students aware of being superior, independent, of character, responsible to themselves, their parents, society and their people. The Research Method collects data obtained through informants, to obtain complete and accurate information, which consists of principals, teachers and primary data managers of secondary data. The results of character education carried out in schools and in the community, carried out by students, teachers and others, in developing character education, training, preparation, and habituation are required. Conclusions made through discussion of the Environment, strategic planning, strategic implementation and evaluation that supports strengths, weaknesses, opportunities and defense, in determining strengths into opportunities, utilizing opportunities to overcome weaknesses, using strengths to protect and exploit weaknesses and challenges.